Portrayal of oral hygiene and risk behaviours in animated movies - Kitsaras, George; Goodwin, Michaela (Frontiers in Oral Health, 2023)
Background Behaviours depicted in movies and TV shows can significantly affect one's behaviour. Children are particularly susceptible to these effects as their habits are still forming. Oral hygiene behaviours play a crucial role in preventing or slowing down the progression of dental diseases, which are among the most common yet preventable diseases in the world. Therefore, it is important to understand if popular movies include oral hygiene behaviours or risk-related behaviours, which can in effect influence children's behaviour. Aim The aim of this study is to review the top grossing animated movies of all time to record and collect on screen portrayals of oral hygiene practices and risk behaviours related to oral health. Methodology Top 30 highest grossing animated feature films (over 40 min duration) were coded using a structured coding instrument to capture oral hygiene and risk-related behaviours related to oral health. Two coders performed coding using the standardised instrument. Results Overall, 93% of behaviours were coded as a risk behaviour, with 7% coded as positive oral hygiene behaviour. Within the risk behaviour category, the majority (74%) were based around the consumption of sugar with risk behaviour occurring in 23 out of 30 movies (76%), while oral hygiene practices occurred in 6 out of 30 movies (20%); one movie depicted neither oral hygiene nor oral health risk behaviours. About 53% of behaviours were purely visual, 10% verbal, and 37% a combination of verbal and visual. Anthropomorphic characters and movie settings resulted in more behaviours related to oral health, either hygiene or mainly risk behaviours, depicted. Conclusion Despite their importance in shaping habits and attitudes, animated movies portrayed a significant number of risk behaviours related to oral health with depiction of beneficial behaviours remaining limited. Consideration should be given on how to best portray behaviours that promote and enhance optimal oral hygiene behaviours to achieve and sustain better oral health for children.